Development and Preliminary Validation of the Coma Arousal Communication Scale. Issue 6 (November 2016) - Garin, Julie; Reina, Margot; DeiCas, Paula; Rousseaux, Marc
Abstract : Objective: To develop a Coma Arousal Communication Scale and perform preliminary validation. Methods: A group of experts developed a questionnaire to assess communication between patients emerging from coma and caregiver (participation, communication modes, and themes) and the strategies used to facilitate communication. To assess the scale's psychometric characteristics, it was presented to the caregivers of 40 inpatients admitted to 5 coma units and (to obtain reference data) to 29 control participants. Results: The Coma Arousal Communication Scale displayed good intra- and interrater reliability as judged by intraclass correlation coefficients (between 0.76 and 0.98) and Bland and Altman plots. Cohen κ coefficient revealed moderate to almost perfect levels of agreement for most individual items and slight levels for a few items dealing with compensatory strategies. We observed good internal consistency, relations with the Wessex Head Injury Matrix, and sensitivity to change for patients who had sustained brain injury in the previous 6 months. Conclusion: The Coma Arousal Communication Scale provides accurate information about communication skills of individuals emerging from coma. However, some compensatory strategies adopted by caregivers are difficult to characterize. Abstract : Supplemental Digital Content is Available in the Text.